Identification of Geothermal Potential with Remote Sensing, Geochemistry, and Magnetotelluric Method in West Sumatera - S S Larasati, I Maratama, P W Laksmana, O D Puspita, I Takodama (Journal of Engineering and Scientific Research, 2020)
West Sumatra is one of a geothermal potential in Indonesia because of interaction between Eurasian and Indo-Australian tectonic. The existence of volcanoes produces geothermal potential with lithology andesite, tuff, and lapilli lava in the Marapi Mountain complex, which elongated at NW-SE direction as a result of NE-SW subduction. The remote sensing method specifically with Composite Band 567 and Lineament Density Analysis (LDA) found anomaly with the permeability value of prospects ranged from 2.05 to 4.76% per km2 (highest density value) with general direction is in the southeast-northwest which in line with the Sumatra structural pattern. Based on geological data, argillic alteration was found with geothermal manifestations consisting of hot springs. Through geochemical analysis, the fluid type of hot water sample (temperature of 48.66oC) is in the immature water zone; occur with the presence of carbonate sinter. Geophysical analysis using the magnetotelluric (MT) method to identified geothermal systems such as cap rock with low resistivity (<30 ohm.m) and reservoirs with moderate resistivity (31-300 ohm.m). The correlation between remote sensing, geochemistry, and magnetotelluric could determine the geothermal potential in West Sumatra.